2022
DOI: 10.1111/1365-2745.13829
|View full text |Cite
|
Sign up to set email alerts
|

Soil fauna accelerate litter mixture decomposition globally, especially in dry environments

Abstract: 1. More than half of the net primary production in terrestrial ecosystems returns to the soil through leaf litter fall and decomposition. In terrestrial ecosystems, litter constitutes a mixture of mainly senescent foliage from multiple species.Yet, the effect of litter mixing on litter decomposition rate remains ambiguous. Quantification of the soil fauna contribution and inclusion of their interaction with litter could remove the prevailing ambiguity, as soil fauna might influence the direction and magnitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 203 publications
(158 reference statements)
1
14
0
Order By: Relevance
“…Reports have indicated that a mesh size of 50 μm permits the entry of micro‐organisms and microfauna, 1 mm permits the entry of micro‐ and mesofauna, and 5 mm permits the entry of the complete decomposer community, including macrofauna (Makkonen et al, 2012). Soil fauna effects on decomposition rates are modulated by climate and litter quality, which vary based on the biome (Njoroge et al, 2022). For instance, García‐Palacios et al (2013) found that the effect of soil fauna on decomposition rates in tropical wet forests is stronger than that in tropical dry forests.…”
Section: Introductionmentioning
confidence: 99%
“…Reports have indicated that a mesh size of 50 μm permits the entry of micro‐organisms and microfauna, 1 mm permits the entry of micro‐ and mesofauna, and 5 mm permits the entry of the complete decomposer community, including macrofauna (Makkonen et al, 2012). Soil fauna effects on decomposition rates are modulated by climate and litter quality, which vary based on the biome (Njoroge et al, 2022). For instance, García‐Palacios et al (2013) found that the effect of soil fauna on decomposition rates in tropical wet forests is stronger than that in tropical dry forests.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, observed rates of decomposition of single species are seldom the same as rates of decomposition when foliage of two or more species are decomposing together 7 , 22 , 23 . While activities of decomposing soil fauna and microbial decomposers (fungi, bacteria etc) are often tightly interrelated 20 , 21 , physical proximity helps determine the biologically facilitated transfers of energy and nutrients, especially from more decomposable tissues to less decomposable tissues.…”
Section: Discussionmentioning
confidence: 99%
“…LIDET 17 , CIDET 18 ). Important findings are that (a) longer-term rates of decomposition are over-estimated by shortterm studies [17][18][19] , (b) litter decomposition is seldom complete and (c) including or excluding important decomposer fauna via the size of litterbag mesh significantly affects measured rates of decomposition 20,21 .…”
mentioning
confidence: 99%
“…Litterbags have significant limitations, including exclusion of larger soil animals from litterbags by using mesh that is smaller than their body width. Previous evidence showed that soil fauna access to the litterbag determines the degree and direction of the influence of litter diversity on litter decomposition (Hättenschwiler & Gasser, 2005; Njoroge et al ., 2022). Confounding factors associated with litterbags include microclimate, handling and leaching losses, and the proportion of fragmented, undecomposed litter that falls or moves out of litterbags in the field.…”
Section: Discussionmentioning
confidence: 99%